Management of BRAF Gene Alterations in Metastatic Colorectal Cancer: From Current Therapeutic Strategies to Future Perspectives - Takeda, Hiroyuki; Sunakawa, Yu (Frontiers in Oncology, 2021)
BRAF mutations constitute an important poor prognostic factor in metastatic colorectal cancer (mCRC) and the development of treatments in this context is of great necessity to prolong patient survival. Although the association between BRAF mutations and microsatellite instability (MSI) has been known for several years, previous clinical trials have revealed that the former has a limited prognostic impact and that immune checkpoint inhibitors offer a significant survival benefit to mCRC patients with both characteristics. Furthermore, the genomic classification of BRAF mutations according to their molecular functions enables greater understanding of the characteristics of mCRC patients with BRAF mutations, with therapeutic strategies based on this classification made more ideal to improve poor prognosis through the delivery of targeted therapies. Recently, a phase III trial was conducted in previously treated mCRC patients with BRAF V600E–mutated tumors and revealed that the combination therapy approach of BRAF inhibition and anti–epidermal growth factor receptor antibody therapy with or without MEK inhibition was more efficacious than standard chemotherapy alone. This review discusses current treatment strategies and future perspectives in BRAF-mutated mCRC.